An exploratory study of serum creatine kinase as a prognostic marker for patients with resectable pancreatic cancer: looking into the relationship with body composition - Cong Chen; Xin Luo; Xianchao Lin; Ronggui Lin; Yuanyuan Yang; Congfei Wang; Haizong Fang; Tianhong Teng; Heguang Huang; Fengchun Lu (Nutrition Journal)
Abstract Background Among cancer patients, pancreatic cancer patients have the highest rate of sarcopenia, which is a critical prognostic factor. Serum creatine kinase (CK) is closely related to skeletal muscle mass and has been reported to decline with the progression of cancer. This study investigated whether preoperative serum CK is associated with the survival of patients with pancreatic cancer. Methods Data were obtained from patients with pathologically confirmed pancreatic cancer between June 2016 and March 2022. The prognostic significance of CK was analyzed based on sex-stratified groups. The Kaplan-Meier method was used to compare overall survival (OS) and disease-free survival (DFS). Multivariate Cox proportional hazards models were used to determine prognostic factors. Body composition was analyzed based on preoperative abdominal CT images to explore the sex-specific associations between skeletal muscle area (SMA) and serum CK levels. Results A total of 166 patients were included in this study. Sarcopenia was presented in 70 patients (42.2%). A low serum CK level showed a significant correlation with the diagnosis of sarcopenia in male patients (P = 0.026). The levels of CK did not predict the outcome in female patients, while a low preoperative CK was notably linked to shorter OS in male patients (median OS: 15 months vs. 33 months, P = 0.011; median DFS: 5 months vs. 14 months, P = 0.007). Multivariate analyses further confirmed the effect of CK in predicting OS (CK>44 IU/L, HR:0.226, 95% CI:0.107–0.478, P < 0.001) and DFS (CK>44 IU/L, HR:0.272, 95% CI:0.139–0.529, P < 0.001) of male patients. Correlation analysis revealed a significant association between SMA and CK levels in male patients (r = 0.225, P = 0.025), and such a correlation was not observed in female patients (r = 0.088, P = 0.478). Conclusion The pretherapeutic CK may represent a simple marker for predicting poor survival in male patients with resectable pancreatic cancer, thereby aiding in the selection of therapeutic strategies.